Fire Evacuation Plan Based on Availability of Time in a Conservation Area - Wahadamaputera S; Subekti B; Duhita D; Pynkyawati T (International Conference on Engineering and Technology Development (ICETD), 2017)
The preservation of buildings in a municipal conservation area is not sufficiently supported by the regulations imposed on the building when it is restored or converted. The immediate area surrounding the conservation building remains a freely constructed area. The existence of the new buildings can unwittingly threaten the continuity of the conserved buildings. Other forms of threat to the preservation of cultural heritage buildings other than demolition are fire hazards that may originate from buildings around preservation objects that may endanger the continuity of conserved buildings. When access to fire-fighting and human-saving assistance is only by dismantling old building, even conservancy  building have to yield.  Consideration to the classification of the conservation building, its location in the downtown area, the situation and the density of the surrounding area, adjacent building function and the architectural style of the conservation building is not enough. The readiness of new buildings in terms of response to the fire ignition, the preparedness of water facilities for fire suppression within 45 minutes, occupants rescue, accessibility of assistance, becomes a matter of concern when the building permit is issued. The prediction of time egress for occupants by utilizing IES (Integrated Environmental Solutions) technology, applied to a design as an example can be used as the basis for designing rescue paths, determining the assembly points as a save destination,  early in the design process. The results of this time calculation can also be used to prepare the postoccupation fire management in the future. The right action based on the available time to save the conservation area's inhabitants and its surroundings, will also save the conservation building